2007
DOI: 10.1212/01.wnl.0000250258.76706.98
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery hypoplasia

Abstract: We determined in 725 sequentially admitted first-ever stroke patients, using color-coded duplex flow imaging of the V2 segment, whether vertebral artery hypoplasia (VAH) (diameter< or = 2.5 mm) was more frequent (13%) in posterior circulation territory infarction (247) than in strokes in other territories (4.6%). This difference is significant (p < 0.001), whereas all other risk factors (hypertension, hyperlipidemia, diabetes, smoking) were equally (p > 0.05) distributed. Patients with VAH may be predisposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 10 publications
12
100
1
5
Order By: Relevance
“…Three prior studies concluded that individuals with hypoplastic vertebral arteries are at increased risk for posterior circulatory stroke more so if they had risk factors like hypertension, diabetes, smoking, etc. [14][15][16]. Our patient had hypoplastic left vertebral artery associated with stenosis in aberrant right subclavian artery proximal to the origin of right vertebral artery leading to relatively compromised blood flow to the brainstem and causing the vertebrobasilar symptoms with minimal exertion of the right upper extremity.…”
Section: Wwwijcasereportsandimagescommentioning
confidence: 77%
“…Three prior studies concluded that individuals with hypoplastic vertebral arteries are at increased risk for posterior circulatory stroke more so if they had risk factors like hypertension, diabetes, smoking, etc. [14][15][16]. Our patient had hypoplastic left vertebral artery associated with stenosis in aberrant right subclavian artery proximal to the origin of right vertebral artery leading to relatively compromised blood flow to the brainstem and causing the vertebrobasilar symptoms with minimal exertion of the right upper extremity.…”
Section: Wwwijcasereportsandimagescommentioning
confidence: 77%
“…Alterations in cerebrovascular haemodynamics may allow for turbulent blood flow, increasing the patient's likelihood of a stroke [7,12]. In fact, hypoplasia of VA has been associated with increased risk of an ischaemic event [4,10,12]. Moreover, lateral displacement of the basilar artery likely contributed to vertebra-basilar insufficiency in this subject [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that hypoplasia of the vertebral artery system puts individuals at risk for stroke of the posterior circulation [18][19]. Such collateral circulations can impede endovascular procedures [20].…”
Section: Discussionmentioning
confidence: 99%